METHOD FOR METALIZATION WITH NICKEL OR COBALT ALLOYS FOR THE MANUFACTURE OF SEMICONDUCTOR DEVICES - Patent application
In 3D NAND memory manufacturing, the electrolyses deposition process of nickel-boron alloy or cobalt-boron alloy is used, combined with the two-step activation process, the conductivity loss problem caused by incomplete word lines filling is solved, and the effect of high conductivity and process simplification is achieved.
Patent Information
- Application Number
- JP2024555976
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-30
- Publication Date
- 2025-04-15
AI Technical Summary
During the manufacturing process of existing 3D NAND memory, word lines filling is difficult to fully realize, resulting in loss of conductivity and memory failure, especially in deeper stacks and finer word lines production.
An improved metallization process is adopted to ensure uniformity and conductivity of the metal layer by electrolysing using nickel-boron alloy or cobalt-boron alloy on a mineral oxide substrate, combined with a two-step activation process.
Deposition of metal layers that maintain high conductivity in extremely thin layers (1-25 nm) is achieved, avoiding conductivity losses, and simplifying the manufacturing process and reducing the number of steps.
Smart Images

Figure 2025510692000001 
Figure 2025510692000002 
Figure 2025510692000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of semiconductors, in particular dynamic random access memories (DRAMs), integrated circuits, and three-dimensional devices such as three-dimensional vertical NAND storage memories (3D-NAND). [Background technology]
[0002] Dynamic Random Access Memories consist of transistor cells and capacitors based on Metal-Oxide-Semiconductor (MOS) technology. The capacitors are usually MIM (Metal-Insulator-Metal) capacitors, consisting of two U-shaped electrodes, i.e. top and bottom electrodes, separated by a dielectric material. The electrodes are based on metal oxides (i.e. RuO2 and SrRuO3, SnO2 and MoO2) or metals (i.e. Pt, TiN, TaN, Ru-Pt, Ta doped with SnO2). The dielectrics can be, for example, Al2O3, TiO2, ZrO2, HfO2, SrTiO3 (STO) or BaSrTiO3 (BST) or ZrO2 stabilized by Y. The electrodes are fabricated by Atomic Layer Deposition (ALD), which is the only approach that has been able to achieve full compliance on structures with complex shapes such as the U-shape. ALD is also the only method that has been able to obtain thin top electrodes. However, these methods reach their limits at the 100 nm technology node. In addition, they must be optimized to increase capacitance density, completely fill cavities, and limit current leakage, such as by reducing the thickness of the metal electrodes without reducing their conductivity.
[0003] A 3D-NAND memory device consists of a semiconductor substrate on which is disposed a stack of alternating layers of conductive material called "word lines," which are essentially metal, and insulating material made from inorganic dielectrics. On the side of the device, the stack may be etched in a "staircase" pattern, with the length and number of layers decreasing from one step to the next in an upward direction.
[0004] In current manufacturing processes, wordlines are created by simultaneously filling several rows of long, narrow horizontal cavities separated by insulating layers with a conductive material; the most commonly used conductive material is tungsten. Tungsten is usually deposited in two steps: an atomic layer deposition (ALD) step to create a thin adhesion layer, followed by a chemical vapor deposition (PECVD) step to completely fill the cavities. However, the further down the stack, the more difficult it becomes to completely fill the stack. This problem is amplified the thinner the wordlines are fabricated and the smaller the cavity openings are. As a result, material voids can form in the tungsten deposit, causing conductivity losses and memory malfunctions. This filling technique therefore shows its limitations, especially in stacks containing 96 or 128 wordlines.
[0005] Moreover, the prior art vapor deposition process tends to deform the silicon specimen and bend it after annealing at the end of the process. To avoid this deformation, it has been proposed to deposit a layer on the backside of the wafer (the frontside is covered by the stack) by a plasma-enhanced chemical vapor deposition (PECVD) process followed by wet etching. However, this method has the disadvantage of adding at least two steps to the manufacturing process of the memory device, and subsequent steps require the control of the backside processing without damaging the frontside.
[0006] As a result, there is a need to provide improved 3D NAND memories, and in particular to fabricate 3D NAND memories in which the word lines have higher conductivity for the same number of levels, and the increased conductivity is achieved by adjusting at least one of two parameters: (1) reducing material voids in the lines, and / or (2) optimizing the volume of conductor available to create the lines.
[0007] Previously, if the word line was tungsten-based, it was necessary to sandwich a thin layer of "blocking" material between the metal line and a blocking dielectric (typically SiO2, optionally associated with alumina Al2O3) that prevents the elements contained in the metal from migrating toward the dielectric. The layer of blocking material reduces the space available for the metal and imposes a height on the space to be filled. An example of a combination of materials sandwiched between the polysilicon channel and the tungsten line is poly-Si / SiO / SiN / SiO2 / Al2O3 / TiN / W. The increased number of successive layers deposited to create the word line significantly limits the volume of the tungsten conductor. In addition, the deposition of additional material adds a step to the fabrication of the memory device.
[0008] In semiconductor devices such as 3D-NAND memories, WO 2021 / 219744 has proposed replacing tungsten word lines with an alloy of nickel and boron. However, although this technology filling technique represents an improvement over the use of tungsten, further modifications are required to create very thin conductive layers.
[0009] There remains a need for a metallization process that can be used in the manufacture of semiconductor devices that allows for the metallization of mineral oxide substrates with a metal layer that remains conductive even at very thin thicknesses, including thicknesses of about 1 to about 25 nm.
[0010] Finally, in three-dimensional integrated circuits, the metal interconnects connecting the electronic components contain copper and are isolated from the semiconductor substrate by layers of barrier materials such as titanium nitride and tantalum nitride. It would be desirable to replace these materials to improve device performance. Summary of the Invention
[0011] It is an object of the present invention to provide an improved metallization method that can be used in the manufacture of semiconductor devices.
[0012] Another object of the present invention is to provide a metallization method that can be used for metallizing mineral oxide substrates.
[0013] Another object of the present invention is to provide a metallization method that allows the metallization of mineral oxide substrates with metal layers that remain conductive at very low thicknesses.
[0014] To that end, in one embodiment, the present invention generally relates to a method for metallizing a mineral oxide substrate with a nickel-boron alloy or a cobalt-boron alloy, the method comprising: a) activating one or more surfaces of a mineral oxide substrate with a precious metal, the activation step comprising: i. a first activation step comprising activating the surface of the mineral oxide substrate by contacting the surface with a first activation solution comprising a solvent, a noble metal complex with a complexing agent, and an organosilane bifunctional linking agent, and thereafter ii. activating, comprising a second activation step comprising activating the surface of the mineral oxide substrate by contacting the surface of the mineral oxide substrate with a second activation solution comprising an aqueous solution at an acidic pH containing precious metal ions; b) contacting one or more surfaces of the mineral oxide substrate with an electroless aqueous solution comprising metal ions and a metal ion reducing agent comprising boron in the absence of electric polarization. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In one embodiment, the present invention generally relates to a method for electroless deposition of an alloy of nickel and boron, comprising activating the surface of a mineral oxide substrate with a noble metal, the activation step comprising: a. a first activation step comprising activating the surface of the mineral oxide substrate by contacting the surface with a first activation solution comprising a solvent, a noble metal complex with a complexing agent, and an organosilane bifunctional linking agent, and thereafter b. A second activation step comprising activating the surface of the mineral oxide substrate by contacting the surface with a second activation solution comprising an aqueous solution at an acidic pH containing precious metal ions.
[0016] Once the surface of the mineral oxide substrate has been activated by the first activation step followed by the second activation step, an alloy of nickel and boron can be deposited on the activated surface of the mineral oxide substrate by electroless deposition.
[0017] As used herein, "a," "an," and "the" refer to both singular and plural references unless the context clearly dictates otherwise.
[0018] As used herein, the term "about" refers to a measurable value, such as a parameter, amount, duration, etc., and is meant to include no more than + / -15% variation, preferably no more than + / -10% variation, more preferably no more than + / -5% variation, even more preferably no more than + / -1% variation, and even more preferably no more than + / -0.1% variation of and from the specifically recited value, so long as such variations are appropriate to practice the invention described herein. It is further to be understood that the value to which the modifier "about" refers is itself specifically disclosed herein.
[0019] As used herein, spatially relative terms such as "beneath," "below," "lower," "above," "upper," and the like are used for ease of description to describe the relationship of one element or feature to another element or feature as illustrated in the figures. It will be further understood that the terms "front" and "back" are not intended to be limiting and are intended to be interchangeable where appropriate.
[0020] As used herein, the terms "comprises" and / or "comprising" specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.
[0021] As used herein, the terms "substantially free" or "essentially free" with respect to a particular element or compound, unless otherwise defined herein, mean that the given element or compound is not detectable by conventional analytical means well known to those skilled in the art of metal plating for bath analysis. Such methods typically include atomic absorption spectroscopy, titration, UV-Vis spectroscopy, secondary ion mass spectrometry, and other commonly available analytical techniques.
[0022] All amounts are percent by weight unless otherwise specified. All numerical ranges are inclusive and combinable in any order, except where it is logical that such numerical ranges are constrained to add up to 100%.
[0023] As used herein, the term "alloy" means a solid solution in which the elements are uniformly distributed.
[0024] In one embodiment, the alloy is a nickel alloy containing boron.
[0025] In another embodiment, the alloy is a cobalt alloy containing boron.
[0026] In one embodiment, the nickel-boron alloy or cobalt-boron alloy may also include at least one of phosphorous and tungsten.
[0027] In addition to nickel (or cobalt) and boron, the alloy may also contain impurities from components present in the aqueous electroless solution.
[0028] The invention also relates to a three-dimensional semiconductor device obtainable by implementing the method described above.
[0029] The method of the invention is particularly applicable to achieving the filling of cavities previously formed in a semiconductor substrate, the dimensions of which at their openings are less than 5 micrometers, or less than 3 micrometers, or less than 1 micrometer, or less than 500 nm, or less than 100 nm, or less than 50 nm, or less than 25 nm, or less than 10 nm.
[0030] As described herein, the method of the invention makes it possible to produce metal deposits on substrates with complex topography in terms of relief and shape, as well as to create metal layers on the walls of cavities whose openings are small in size and large in depth, in particular to overcome materials used in the prior art as barriers to the diffusion of copper or other metals.
[0031] The process of the invention allows for the deposition of a metal layer directly on an inorganic dielectric material, which may be a mineral oxide substrate, which may be selected from, by way of example and not limitation, silicon dioxide (SiO2), alumina (Al2O3), hafnium oxide, zirconium oxide, and their silicates.
[0032] The process of the present invention also makes it possible to eliminate the need for deposition of a barrier layer, generally titanium nitride or tantalum nitride, more generally titanium nitride. The absence of a barrier material provides the advantage of eliminating a step in the process without reducing the electrical conductivity of the metal line. The inventors of the present invention have discovered that nickel-boron (or cobalt-boron) alloys do not diffuse into dielectrics. Nickel-boron (or cobalt-boron) alloys used as conductors instead of tungsten not only exhibit barrier properties, but also provide higher electrical conductivity than tungsten.
[0033] The alloy deposition step can advantageously be carried out by subjecting the mineral oxide surface to ultrasound. The mineral oxide with which the electroless solution comes into contact can be, for example, SiO2 or Al2O3.
[0034] The nickel or cobalt alloy deposits may be formed at various stages of the 3D NAND memory manufacturing process. For example, the alloy may be deposited to form the word lines, to form contacts between the polysilicon channel and the bit lines, or to form a barrier layer for the bit lines.
[0035] In one embodiment, the process of the present invention is used to metallize a mineral oxide substrate with nickel-boron or cobalt-boron alloys in the process of fabricating 3D NAND devices.
[0036] The present application also describes a method for metallizing a semiconductor substrate, said substrate comprising at least one horizontal cavity opening onto a vertical cavity, said horizontal cavity having a smaller opening size than said vertical cavity, said cavity defining a surface comprising at least one region of inorganic oxide, said metallization method comprising the steps of selectively activating the inorganic oxide surface and thereafter depositing a metal on the activated inorganic oxide surface in the absence of polarization by contacting said surface with an electroless solution comprising metal ions, preferably nickel or cobalt ions, in combination with a suitable reducing agent for the metal ions.
[0037] In one embodiment, the present invention generally relates to a method for metallizing one or more surfaces of a mineral oxide substrate with an alloy of nickel and boron by electroless deposition. Prior to electroless deposition, one or more surfaces of the mineral oxide substrate are activated with a precious metal.
[0038] This activation step is a. a first activation step comprising activating the surface of the mineral oxide substrate by contacting the surface with a first activation solution comprising a solvent, a noble metal complex with a complexing agent, and an organosilane bifunctional linking agent, and thereafter b. A second activation step comprising activating the surface of the mineral oxide substrate by contacting the surface with a second activation solution comprising an aqueous solution at an acidic pH containing precious metal ions.
[0039] The mineral oxide substrate may be selected from silicon dioxide (SiO2), alumina (Al2O3), hafnium oxide, zirconium oxide, and silicates thereof.
[0040] In the first activation step, one or more surfaces of the mineral oxide substrate are contacted with a first activation solution, the first activation solution including a precious metal complex and an organosilane coupling agent in combination with one or more solvents.
[0041] In one embodiment, the precious metal may be selected from the group consisting of ruthenium, rhodium, osmium, iridium, palladium, platinum, gold and silver, which are complexed with a complexing agent to form a precious metal complex, hi one embodiment, the precious metal comprises palladium, which is complexed with a suitable complexing agent to form a palladium complex.
[0042] In one embodiment, the palladium complex may be selected from (NH4)2(PdCl4), Pd(NH3)4, and a complex of formula (I):
[0043] [ka] During the ceremony, R1 and R2 are the same and represent H, CH2CH2NH2, CH2CH2OH, or R1 represents H and R2 represents CH2CH2NH2, or R1 represents CH2CH2NH2 and R2 represents CH2CH2NHCH2CH2NH2, or R1 represents H and R2 represents CH2CH2NHCH2CH2NHCH2CH2NH2; X is Cl-, Br - , I - , H2O, NO.3 - , CH3SO3 - , CF3SO3 - , CH3-Ph-SO3 - , CH3COO - represents a ligand selected from the group consisting of:
[0044] In one embodiment, the palladium complex is a complex having formula (I) in which R1 and R2 represent H and X represents Cl.
[0045] In one embodiment, the first activation solution comprises a precious metal complex or a plurality of precious metal complexes in a concentration of 10 -6 M~10 -2 M, preferably 10 -5 M~10 -3 M, preferably 5-10 -5 M~5·10 -4 Contains a concentration of M.
[0046] According to a particular feature of the invention, the organosilane coupling agent used in the first activation solution may have the general formula (II): {X-(L)} 3-n Si(OR) n (II) During the ceremony, X represents a functional group selected from the group consisting of thiol, pyridyl, epoxy (oxacyclopropanyl), glycidyl, and a primary amine capable of reacting with a simple palladium compound or with formula (I); L represents a spacer arm selected from the group consisting of CH2, CH2CH2, CH2CH2CH2, CH2CH2CH2CH2, CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2, CH2CH2CH2NHCH2CH2CH2, CH2CH2CH2NHCH2CH2CH2CH2CH2CH2CH2CH2CH2, Ph, Ph-CH2, and CH2CH2-Ph-CH2 (Ph represents a phenyl ring); R is a group selected from the group consisting of CH3, CH3CH2, CH3CH2CH2, (CH3)2CH; n is an integer equal to 2 or 3.
[0047] The organosilane coupling agent may also have the general formula (III): (OR)3Si-(L)-Si(OR)3(III) During the ceremony, L represents a spacer arm selected from the group consisting of CH2CH2CH2NHCH2CH2NHCH2CH2 and CH2CH2CH2-SS-CH2CH2CH2; R is a group selected from the group consisting of CH3, CH3CH2, CH3CH2CH2, (CH3)2CH.
[0048] Compounds of formula (II) or (III) can be, for example, the following compounds: (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, p,m-aminophenyltrimethoxysilane, 4-aminobutyltriethoxysilane, m,p(aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 2-(4-pyridylethyl)triethoxysilane, bis(3-trimethoxysilylpropyl)ethylenediamine, (3-trimethoxysilylpropionyl)
[0043] The compound is selected from the group consisting of N-(3-trimethoxysilylethyl)diethylenetriamine, N-(3-trimethoxysilylethyl)ethylenediamine, N-(6-aminohexyl)aminopropyltrimethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, 5,6-epoxyhexyltriethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, bis[3-(triethoxysilyl)propyl]disulfide, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, (p-chloromethyl)phenyltrimethoxysilane, and m,p((chloromethyl)phenyl)trimethoxysilane.
[0049] Examples of organosilane coupling agents that may be used in the context of the present invention include (3-aminopropyl)-trimethoxy-silane, (3-aminopropyl)-triethoxy-silane, [3-(2-aminoethyl)aminopropyl]trimethoxy-silane and 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane.
[0050] In one embodiment, the organosilane bonding agent comprises at least two amino groups, or even at least three amino groups including a primary amine and two secondary amines.
[0051] The concentration of the organosilane coupling agent is preferably about 10 -5 M ~ about 10-1 M, preferably about 10 -4 M ~ about 10 -2 M, preferably about 5·10 -4 M ~ approx. 5·10 -3 It's M.
[0052] The solvent of the first activation solution may include one or more solvents selected from the group consisting of N-methylpyrrolidinone (NMP), dimethyl sulfoxide (DMSO), alcohol, ethylene glycol ethers such as monoethyl-diethylene glycol (EDEG), propylene glycol ethers, dioxane, and toluene.
[0053] In one embodiment, the first activation solution comprises (ethylenediamine)palladium(II) chloride and 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane in DMSO as a solvent.
[0054] The first activation step is preferably carried out at a temperature in the range of 50° C. to 80° C., for example 60° C. to 70° C. The first activation step is generally carried out for a period of about 30 seconds to about 30 minutes, more preferably about 5 minutes to about 30 minutes. The pH of the first activation solution may be in the range of 2 to 10.
[0055] Contacting the mineral oxide substrate with the first activation solution may be carried out by immersing a test specimen having a mineral oxide surface in a vessel containing the above-mentioned first activation solution, and optionally applying ultrasound.
[0056] After the mineral oxide substrate has been in contact with the first solution for a sufficient period of time, the activated surface or surfaces of the mineral oxide substrate are rinsed to remove all traces of the first activation solution.
[0057] The first activation step results in the formation of an activated surface. This first activation step is then followed by a second activation step in which the activated surface is contacted with a second aqueous activation solution having a pH in the range of 1 to 4 and containing precious metal ions. In one embodiment, the precious metal ions are selected from the group consisting of ruthenium ions, rhodium ions, osmium ions, iridium ions, palladium ions, platinum ions, gold ions, silver ions, and combinations thereof. In one embodiment, the precious metal ions are palladium ions, preferably Pd 2+ ions. In one embodiment, the precious metal used in the first activation solution is the same as the precious metal used in the second activation solution.
[0058] The second activation solution may be prepared by dissolving a source of precious metal ions in water and then adjusting the pH to 1 to 4, preferably 1.5 to 2.5. In one embodiment, the source of precious metal ions is a compound selected from the group consisting of tetrachloropalladium acid, palladium(II) trifluoroacetate, palladium(II) pivalate, palladium(II) trimethylacetate, and palladium(II) acetate. In one embodiment, the concentration of the source of precious metal ions is about 10 -8 M ~ about 10 -1 M, more preferably about 10 -6 M ~ about 10 -2 M. If necessary, a pH adjuster including a mineral acid such as sulfuric acid, nitric acid, phosphoric acid or hydrochloric acid may be added to the solution.
[0059] The second activation step is carried out at a temperature ranging from about 15° C. to about 40° C., more preferably from about 20° C. to about 25° C. The duration of the second step can be from 5 seconds to 60 seconds. Contacting the activated mineral oxide surface with the second aqueous solution can be carried out by immersion in the second activation solution described above.
[0060] After the activated mineral oxide substrate has been in contact with the second aqueous solution for a sufficient period of time, the activated mineral oxide surface is rinsed to remove all traces of the second solution.
[0061] Without wishing to be bound by theory, the present inventors believe that the two-step activation process described herein allows for complete coverage of the vertical substrate surface with activator, allowing for a continuous conductive layer at very low thickness for subsequent electroless deposition.
[0062] That is, while our US Provisional Patent Application No. 63 / 307,234 requires both boron and either phosphorus or tungsten in the alloy at the atomic percentages (atomic %) listed to produce a more conductive deposit, especially at very thin thicknesses, the present invention does not require the presence of tungsten or phosphorus in the alloy to achieve such a conductive deposit at extremely thin thicknesses. That is, in one embodiment, the nickel-boron or cobalt-boron alloy described herein is at least essentially free of tungsten and phosphorus, meaning that the alloy does not contain tungsten or phosphorus beyond the amount present as an impurity from components present in the electroless plating solution. In another embodiment, the nickel-boron or cobalt-boron alloy contains a small amount of tungsten or phosphorus, such as less than 0.1 atomic %, or less than 0.01 atomic %, or less than 0.001 atomic % of tungsten and / or phosphorus.
[0063] Once the two-stage application process is complete, the activated mineral oxide substrate may be contacted with an electroless plating solution containing metal ions, preferably one or more of nickel and cobalt ions, along with a reducing agent comprising boron to deposit a nickel-boron or cobalt-boron alloy onto the activated surface of the mineral oxide substrate. In one embodiment, this may be accomplished by contacting the activated mineral oxide surface with an aqueous electroless solution containing nickel or cobalt ions and a nickel or cobalt ion reducing agent comprising boron.
[0064] The contacting is carried out on the surface of the mineral oxide substrate under conditions that allow the formation of a layer of nickel-boron alloy or cobalt-boron alloy having a thickness of, for example, at least 5 nanometers, for example a thickness in the range of 5 nm to 20 nm, or 7 nm to 15 nm, or 7 nm to 10 nm.
[0065] The average resistivity of this nickel-boron or cobalt-boron alloy layer, measured by methods known to those skilled in the art, such as a four-point probe at different points in the sample, may be in the range of 20 to 300 μΩ.cm, preferably 20 to 200 μΩ.cm, or 20 to 150 μΩ.cm.
[0066] The resistivity of the alloy layer is preferably less than 300 μΩcm when the layer thickness is 20 nm or less, and is, for example, 80 to 120 μΩ.cm when the layer thickness is 5 nm to 15 nm.
[0067] The method of the invention makes it possible to obtain a layer of nickel-boron or cobalt-boron alloy that is conductive when its thickness is between 5 nm and 14 nm. The term "conductive layer" within the meaning of the invention refers to a layer whose resistivity value is obtained by a measurement method known to the person skilled in the art, for example by the four-point method. For comparison, prior art methods in which the activation step only includes the first step described above are not able to form a layer of nickel alloy and boron that is conductive when its thickness is less than or equal to 14 nm.
[0068] In a particular embodiment, the method of the invention makes it possible to obtain a layer of nickel alloy and boron having a smaller thickness than the metal layer obtained according to the teachings of WO 2021 / 219744 and having equal electrical conductivity values.
[0069] The boron-containing nickel ion reducing agent is preferably used in a sufficient amount such that boron constitutes 0.1 atomic % to 10 atomic %, more preferably about 0.1 atomic % to about 5.0 atomic %, more preferably about 0.1 to about 3.0 atomic % in the nickel or cobalt alloy. The nickel (or cobalt) ions are present in the nickel-boron or cobalt-boron alloy in an amount sufficient such that nickel (or cobalt) constitutes 90 atomic % to 99.9 atomic %, more preferably about 95 atomic % to about 99.9 atomic %, more preferably about 97.0 atomic % to about 99.9 atomic %.
[0070] The aqueous electroless solution can be obtained by dissolving a nickel metal salt, preferably selected from the group consisting of acetates, acetylacetonates, hexafluorophosphates, nitrates, perchlorates, sulfates or nickel tetrafluoroborate, in water. A hydrated form of one of the listed nickel salts may also be used. In one embodiment, the nickel salt is nickel sulfate hexahydrate. The nickel ions are, for example, 10 -2 The concentration is from 50 mM to 1M, preferably from 50 mM to 500 mM.
[0071] In the case of electroless cobalt solutions, the cobalt ions are introduced into the electroless solution as inorganic cobalt salts, such as chlorides and / or sulfates, or other inorganic salts or complexes, such as pyrophosphates, or cobalt complexes with organic carboxylates, such as acetates, citrates, lactates, succinates, propionates, and hydroxyacetates. -2 The concentration is from 50 mM to 1M, preferably from 50 mM to 500 mM.
[0072] The boron-containing reducing agent may be a borane derivative, such as a borane derivative selected from dimethylaminoborane, pyridine borane, morpholene borane, and tertbutylamine borane.
[0073] The electroless aqueous solution optionally contains at least one nickel ion stabilizer, preferably 10 -3 The amount is M~1M.
[0074] The aqueous electroless solution may contain a nickel ion stabilizer selected from the group consisting of ethylenediamine, citric acid, acetic acid, succinic acid, malonic acid, aminoacetic acid, malic acid, or the alkali metal salts of these compounds. A preferred stabilizer for the present invention is citric acid, which forms a complex with the nickel ions in solution.
[0075] The electroless aqueous solution may contain an agent to adjust the pH to a value between 6 and 11. In one embodiment, the pH of the aqueous solution ranges from 8 to 10, more preferably from 9.0 to 9.5. The pH adjuster may be selected from the group consisting of aminoethanol, N-methylaminoethanol, and N,N-dimethylaminoethanol. A preferred pH adjuster is N-methylaminoethanol.
[0076] The electroless aqueous solution may further contain a polyamine, preferably an aliphatic polyamine, in a concentration that may be from 1 ppm to 1000 ppm (mg / L). In a preferred embodiment, the electroless solution contains polyethyleneimine, preferably with a molecular weight of 500 g / mol or more, more preferably greater than about 600 g / mol, more preferably greater than about 700 g / mol. Alternatively, the solution may contain a polymer selected from derivatives of chitosan, poly(allyl-amine), poly(vinyl-amine), poly(vinyl-pyridine), poly(amino-styrene), poly(L-lysine), and the acid (or protonated) forms of these polymers.
[0077] Contacting the substrate with the electroless solution may be carried out by immersing the mineral oxide substrate in the above-mentioned solution for a period of 30 seconds to 15 minutes, more preferably about 1 minute to about 10 minutes, depending on the thickness of the nickel alloy desired, at a temperature of 40° C. to 90° C., preferably 60° C. to 70° C. Contacting with the electroless solution is advantageously carried out for a sufficient time to obtain a nickel alloy or cobalt alloy layer having a thickness of more than 1 nm to less than 25 nm, more preferably 4 nm to 10 nm.
[0078] The deposition process of the alloy metal layer can be carried out under different conditions. For example, the substrate to be coated may be rotated. A recirculation of the electroless solution can be imposed in the reactor. The contact of the substrate with the electroless solution can be carried out by wetting by spraying the solution at high pressure. Other means can be used in a complementary manner, for example by agitating the substrate and / or the solution using ultrasound or megasound. In all cases, the contact can be carried out under high vacuum. The surface to be coated can be placed face up or face down.
[0079] According to an advantageous embodiment, this layer may be annealed at a temperature between 200° C. and 700° C., preferably 400° C., for a period between 1 minute and 30 minutes, preferably about 10 minutes, under an inert or reducing atmosphere (e.g. 4% hydrogen in nitrogen).
[0080] An example of an electroless aqueous solution includes: a)10 -2 M to 1M, preferably 50 mM to 500 mM, of nickel ions or cobalt ions; b)10 -1 at least one reducing agent containing boron at 400 mM to 1M, preferably 400 mM to 600 mM, c) optionally, one or more nickel or cobalt ion stabilizers; d) optionally a pH adjuster; e) 5 mg / L to 1000 mg / L (or ppm) of an amino polymer, preferably polyethyleneimine, more preferably having a molecular weight in the range of 500 to 25,000 g / mol, more preferably about 600 to about 20,000 g / mol, more preferably about 700 to about 15,000 g / mol, more preferably about 800 to about 10,000 g / mole, more preferably about 1,000 to about 5,000 g / mol, and residual water.
[0081] In one embodiment, the electroless solution consists essentially of the recited components. By "consisting essentially of," it is meant that the electroless solution does not contain any components that detrimentally affect electrical conductivity, including concentrations of boron, phosphorous, and / or tungsten above the ranges defined herein.
[0082] In one embodiment, the electroless solution is comprised of the ingredients listed to provide an electroless nickel or cobalt alloy layer on a mineral oxide substrate that exhibits good electrical conductivity at very low thicknesses.
[0083] The step of depositing the alloy metal layer may be carried out under different conditions. For example, in one embodiment, the substrate to be coated may be rotated. A recirculation of the electroless solution may be imposed in the reactor. The substrate may be contacted with the electroless solution by spray wetting with the solution at high pressure. Other means may also be used in a complementary manner, for example by agitating the substrate and / or the solution with ultrasound or an ultrasonic gun. In both cases, the contacting may be carried out under high vacuum.
[0084] In addition to the selective metallization process, the method for manufacturing a 3D NAND memory according to the present invention may include other steps necessary to provide a functional memory device, or the method may include steps in addition to those described above to provide only a portion of the memory device.
[0085] A first example of a 3D NAND memory obtained according to the method of the present invention includes a semiconductor substrate defining a horizontal plane, at least one semiconductor channel arranged along a vertical axis, and several word lines including a nickel or cobalt alloy.
[0086] The method for manufacturing such a memory may include at least one other step in addition to the metallization process. For example, the method of the invention may include the following steps before the steps of activation and electroless deposition of a nickel or cobalt alloy: - manufacturing or providing a stack of parallel layers comprising at least two layers of a sacrificial material, such as SiN or polysilicon, arranged on a semiconductor substrate and separated by a first insulating material, such as SiO2, the stack having a vertical face opening onto a cavity whose largest dimension is along a vertical axis, - selectively etching the sacrificial material to form at least two horizontal cavities opening onto a cavity whose axis is vertical;
[0087] These two steps are followed by selectively depositing a nickel or cobalt alloy into the horizontal cavities by the electroless process described above. The selective deposition step ensures that the vertical cavities are not filled with nickel or cobalt alloy after the step is completed.
[0088] The vertical cavities may have an average opening diameter in the range of 80 nm to 150 nm and a depth of greater than 1 micron, and the horizontal cavities may have an average width along the vertical axis that is smaller than the average opening diameter of the vertical cavities.
[0089] The method of the present invention provides a particularly advantageous alternative for the manufacture of 3D NANDs containing more than 90 wordlines of tungsten or other physically deposited metals. The substrates used in the manufacture of such 3D NANDs, which are in contact with the electroless solution (also called electrolyte) described above, may contain a number of layers selected from the group consisting of 32, 48, 64, 96, 128, 192, 256, preferably 96 or 128, or more.
[0090] In this substrate, the vertical cavities have, in particular, an average diameter at the opening less than 1 micron, for example in the range of 50 nm to 150 nm, and a depth greater than 1 micron, and the horizontal cavities have an average width along the vertical axis less than 100 nanometers and an average depth along the horizontal axis less than 100 nanometers.
[0091] According to a second example of the process of the present invention, the nickel or cobalt alloy deposits form at least a part of the electrical contacts between different functional conductive elements of the 3D NAND device. These contacts may be located between the bit lines and the semiconductor channel (referred to herein as "contacts"). These contacts may also be located between the power lines and the word lines (referred to herein as "periphery contacts").
[0092] According to a third example, a 3D NAND memory obtained according to the method of the present invention includes a semiconductor substrate defining a horizontal plane, at least one semiconductor channel disposed along a vertical axis, and at least one bit line comprising a nickel or cobalt alloy deposited according to the metallization process of the present invention.
[0093] The features of the metallization process described above, including the features of carrying out the steps of activating with a noble metal and contacting the activated substrate with an electroless solution, apply to all three embodiments of the method according to the invention.
[0094] The manufacturing method according to the invention may include at least one other step in addition to the metallization process. For example, the method according to the invention may include a step of depositing a layer of dielectric material, followed by a step of etching a cavity in the dielectric material by photolithography, before the step of activation and electroless deposition of a nickel or cobalt alloy. The walls of the dielectric cavity are then activated with a noble metal and metallized with a nickel or boron alloy as described above.
[0095] The invention also relates to a semiconductor device obtainable by implementing the method described above.
[0096] In fact, the metallization method of the invention can be used in the manufacture of three-dimensional semiconductor devices such as MIM capacitors forming part of the structure of three-dimensional integrated circuits or 3D NAND type storage memories, or V-DRAM storage memories or DRAM storage memories, at the level of the creation of conductive lines.
[0097] The metallization method of the invention can be used, for example, for the manufacture of copper conductive lines, which comprises a step of depositing a nickel alloy on the walls of mineral oxide cavities intended to be filled with copper in a subsequent step. These cavities have, for example, an average diameter at their opening ranging from 10 nm to 30 nm and a depth ranging from 20 nm to 100 nm. The average diameter at the opening of the cavities is preferably less than 500 nm, for example less than a value selected from the group consisting of 400 nm, 300 nm, 200 nm, 100 nm, 50 nm and 10 nm.
[0098] The invention is illustrated by the following examples, in which the temperature is between 20° C. and 25° C., unless otherwise stated, and the pressure is equal to atmospheric pressure.
[0099] Example 1: Deposition of a thin conductive layer of nickel-boron alloy In this example, the substrates used were SiO coupons, each piece having dimensions of 4 cm x 4 cm, a thickness of 750 μm, with openings of about 10 μm and vertical cavities with a height of about 100 micrometers.
[0100] (a) Cleaning the cavity surface: The specimen is cleaned according to the chemical nature of the substrate. After this cleaning step, the specimen is rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water, and subjected to ultrasound (40 kHz) for 2 minutes.
[0101] b) Activation of the cavity surface in two steps: First activation step: In a beaker, 350 microliters of 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane and 15 mg of (ethylenediamine)palladium(II) chloride were dissolved in 80 mL of dry DMSO (max. 50 ppm H2O) at 7.9·10 -4A first activation solution is obtained, which contains M of palladium complex and 24.4 mM of silane compound. The test piece prepared in step a1) is immersed in a beaker containing the first activation solution at a temperature of 65° C. under ultrasound for 15 minutes. The test piece is removed from the first activation solution, rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water and subjected to ultrasound (40 kHz) for 30 seconds. The test piece is removed from the beaker and rinsed thoroughly with deionized water. Second stage of activation: The specimens were then treated with 10% -3 The specimen was immersed in a solution of HPdCl4 at 1000 mol / L, pH 2.0 for 30 seconds. The specimen was removed from the solution, rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water, and subjected to ultrasound (40 kHz) for 30 seconds. The specimen was then removed from the beaker and rinsed thoroughly with deionized water.
[0102] c) Deposition of a layer of metallic NiB by electroless deposition: c1) Pre-preparation of the electroless solution: In a 1 liter vessel, in a minimum amount of deionized water, 31.11 g of nickel sulfate hexahydrate (0.118 mol), 44.67 g of citric acid (0.232 mol), 52.26 g of N-methylaminoethanol (0.700 mol) and 2.5 ppm of polyethyleneimine (PEI) (Mn=600 g / mol) are introduced in this order. The final pH is adjusted to 9.3 with N-methylaminoethanol and the total volume is adjusted to 1 liter with deionized water. To the 9 volumes of the previous solution, a volume of reducing solution is added immediately before the next step. The latter contains 28 g / L of dimethyl-amino borane (DMAB, 0.475 mol) and 60.00 g of N-methylaminoethanol (0.798 mol). c2) Forming a NiB alloy layer on the alumina layer: A nickel-boron alloy layer was deposited on the surface of the substrate treated in step b) by first immersing the substrate in a beaker of deionized water and then immersing the substrate in a previously prepared electroless solution heated to 65° C. for a period ranging from 1 to 6 minutes. A grey, shiny metal coating is then observed on the specimen. The specimen is removed from the solution, rinsed thoroughly with deionized water, immersed in a beaker filled with deionized water and subjected to ultrasound (40 kHz) for 30 seconds. The specimen is then removed from the beaker, rinsed thoroughly with deionized water and dried under a nitrogen flow. The specimen is subjected to Rapid Thermal Annealing (RTA) at 400° C. for 10 minutes in a reducing atmosphere (4% hydrogen in nitrogen). The operation can be carried out using a tubular oven or a hot plate.
[0103] (d) Characteristics of the metal deposit filling the cavity The vertical cavity is covered with a thin continuous layer of nickel-boron alloy, the thickness of which is measured under a microscope at 150,000 times magnification. The continuity of the layer, i.e. the thickness at which the NiB particles are connected and the electrical conductivity is measurable, is obtained in a deposition process lasting 2 minutes. In this case, a thickness of 7 nm and a resistivity of 110 μΩ.cm are measured. The resistivity was measured using a reference device (Automatic 4-Point Probe Meter MODEL 280 available from FOUR Dynamics Inc.).
[0104] Example 2 Comparison: Deposition of a nickel-boron alloy layer by a method of the prior art Example 1 was repeated, except that activation of the cavity surfaces was included in the first stage activation (ie, the second stage activation was not completed).
[0105] After thermal annealing of the specimen obtained at the end of step c2), it is observed that all vertical cavities are covered with a thin layer of nickel-boron alloy with a thickness of 18-40 nm depending on the deposition time. The continuity of the layer, i.e. the thickness at which the nickel-boron alloy metal particles are connected and the electrical conductivity becomes measurable, is obtained after a deposition time of 3.5 minutes. In this case, a thickness of 18 nm is measured and the resistivity is 330 μΩ.cm.
[0106] The results of the resistivity measurements carried out in Example 1 and Comparative Example 2 are shown in Table 1.
[0107] [Table 1]
[0108] The results show that at very low thicknesses, the two-step activation process described herein produces deposits that exhibit good electrical conductivity that is not achievable by comparative processes that use only a single activation step.
Claims
1. 1. A method for metallizing a mineral oxide substrate with a nickel-boron or cobalt-boron alloy, said method comprising: a) activating one or more surfaces of said mineral oxide substrate with a precious metal, said activating step comprising: i. a first activation stage comprising activating the surface of the mineral oxide substrate by contacting the surface with a first activation solution comprising a solvent, a noble metal complex with a complexing agent, and an organosilane bifunctional linking agent, and thereafter ii. Activating, comprising a second activation stage comprising activating the surface of the mineral oxide substrate by contacting the surface with a second activation solution comprising an aqueous solution at an acidic pH containing precious metal ions; b) contacting one or more surfaces of said mineral oxide substrate with an aqueous electroless solution comprising metal ions and a metal ion reducing agent comprising boron in the absence of electric polarization.
2. 2. The method of claim 1, wherein the precious metal of the first activation step is selected from the group consisting of ruthenium, rhodium, osmium, iridium, palladium, platinum, gold, silver, and combinations thereof, and the precious metal is complexed with a complexing agent to form the precious metal complex.
3. The method of claim 1 or 2, wherein the complexing agent comprises ethylenediamine.
4. 3. The method of claim 2, wherein the precious metal comprises palladium, and the palladium is complexed with a suitable complexing agent to form a palladium complex.
5. The concentration of the precious metal complex in the first activation solution is about 10 -6 M ~ about 10 -2 The method according to any one of claims 1 to 3, wherein M is in the range of
6. The method of any one of claims 1 to 3, wherein the organosilane coupling agent in the first activation solution contains two or three amine functional groups.
7. The method of claim 6, wherein the organosilane coupling agent in the first activation solution comprises 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane.
8. The concentration of the organosilane coupling agent in the first activation solution is 10 -5 M to 10 -1 The method according to any one of claims 1 to 3, wherein M is
9. The method according to any one of claims 1 to 3, wherein the first activation step is carried out at a temperature in the range of from 50°C to 80°C.
10. The method according to any one of claims 1 to 3, wherein the first activation step is carried out for a period ranging from 30 seconds to 30 minutes.
11. 2. The method of claim 1, wherein the precious metal ions of the second activation solution are selected from the group consisting of ruthenium ions, rhodium ions, osmium ions, iridium ions, palladium ions, platinum ions, gold ions, silver ions, and combinations thereof.
12. The noble metal ion is a palladium ion, preferably Pd 2+ The method of claim 11 , comprising ions.
13. 2. The method of claim 1, wherein the second activation solution is obtained by dissolving in water at least one compound selected from tetrachloropalladium acid, palladium(II) trifluoroacetate, palladium(II) pivalate, palladium(II) trimethylacetate and palladium(II) acetate.
14. The method of claim 1 , wherein the precious metal used in the first activation solution is the same as the precious metal used in the second activation solution.
15. 2. The method of claim 1, wherein the second activation step is carried out at a temperature ranging from 15° C. to 40° C. for 5 to 60 seconds.
16. The mineral oxide substrate is HfO 2 , SiO 2 , and Al 2 O 3 The method of claim 1 , wherein the compound is selected from the group consisting of:
17. The method according to any one of claims 1 to 16, further comprising a step of rapid thermal annealing of the nickel or cobalt alloy layer formed on the surface of the mineral oxide substrate.
18. A three-dimensional semiconductor device obtainable by carrying out the method according to any one of claims 1 to 17.